2015
DOI: 10.1039/c5lc00180c
|View full text |Cite
|
Sign up to set email alerts
|

Differentiation of neuroepithelial stem cells into functional dopaminergic neurons in 3D microfluidic cell culture

Abstract: A hallmark of Parkinson's disease is the progressive loss of nigrostriatal dopaminergic neurons. We derived human neuroepithelial cells from induced pluripotent stem cells and successfully differentiated them into dopaminergic neurons within phase-guided, three-dimensional microfluidic cell culture bioreactors. After 30 days of differentiation within the microfluidic bioreactors, in situ morphological, immunocytochemical and calcium imaging confirmed the presence of dopaminergic neurons that were spontaneously… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
110
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 132 publications
(116 citation statements)
references
References 47 publications
(83 reference statements)
5
110
0
1
Order By: Relevance
“…It is based on a 384-well microtiter plate format and employs coverslip-thickness glass (175 μm) for optical access. A plate comprises 96 microfluidic tissue chips, which each can be used to establish a miniaturized tissue model171819. Each chip connects four neighboring wells: one well is used for administering the cell/ECM mixture, two wells for supplying growth medium, and a fourth well for imaging (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…It is based on a 384-well microtiter plate format and employs coverslip-thickness glass (175 μm) for optical access. A plate comprises 96 microfluidic tissue chips, which each can be used to establish a miniaturized tissue model171819. Each chip connects four neighboring wells: one well is used for administering the cell/ECM mixture, two wells for supplying growth medium, and a fourth well for imaging (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…As microfluidic technology matures, the focus will shift towards biological development and validation of physiologically relevant models (Figure 4). The trend for the coming years will be to use microfluidic 3D cell culture in combination with the recent advances in stem cell biology, such as iPSC [64] and organoid technology. This will allow to take into account differences between patients in various applications: first, novel diagnostic tests to predict treatment outcome for an individual patient; second, supporting clinical trial design; or third, taking the individual differences already into account during drug discovery and developments, both in respect to efficacy and toxicity.…”
Section: Microfluidics and 3d Cell Culture: From Exploration To Validmentioning
confidence: 99%
“…In this regard a study investigated the application of 3D microfluidic cell culture technology for differentiation of NEPSCs derived from human iPSC to DNs (Fig 6. D,E) 58 . After 30 days DNs were produced that were electrophysiologically active, and exhibited long neurites typical of mature neurons forming an interconnected network in this biocompatible phase-guided microfluidic cell culture bioreactor.…”
Section: Stem Cells In Microfluidic-based Neural Tissue Engineeringmentioning
confidence: 99%
“…In addition placenta-derived multipotent stem cells (PDMCs) can be obtained from human placenta with the potential to differentiate into different cell lineages without any ethical problems 57 . Some studies have reported derivation of neuroepithelial stem cells (NEPSCs) from ESCs with the potential to differentiate into neural tube and neural crest lineages under the appropriate biochemical conditions 58, 59 .…”
Section: Stem Cells and Tissue Engineeringmentioning
confidence: 99%